CEO WANITA, KEPUTUSAN INVESTASI, DAN KEPUTUSAN PENDANAAN - Rahmat Setiawan; Zuhroida Bella Meilina; Fisca Fideline Palullungan (LPSDI Bina Patria, 2025)
The purpose of this research is to verify the influence of female CEOs on investment and financing decision in manufacturing companies which listed on the Indonesia Stock Exchange. This research uses multiple linear regression models and logistic regression models. The data is acquired from Companies Annual Report Published period 2013-2017. The dependent variables in this research are the level of investment, acquisition decisions, and leverage. The independent variable used in this reseach is female CEO proxied with dummy variable which worth 1 if the company is led by a female CEO, and is worth 0 if vice versa. The finding of this research show that (1) companies led by female CEOs (2) companies led by female CEOs tend not to make acquisitions compared to companies not led by female CEOs, and (3) companies led by female CEOs have lower leverage than companies not led by female CEOs.